Optimization of size and timing of base salary increases. Issue 2 (3rd April 2019) - Cokyasar, Taner; Garcia-Diaz, Alberto; Jin, Mingzhou
Abstract: Salary administration research mostly examines the compensation guides in a subjective manner and lacks quantitative approaches. Recent failure instances of salary administration demonstrate the exiguity and/or inapplicability of scientific research in this area. This research considers the core aspects of theoretical salary administration while complying with the recent competitive working environment. In this article, a mathematical optimization approach that recognizes the significance of performance and potential to future promotions of employees is proposed to find the optimal salary increase amounts and to set an advantageous schedule for salary increases. The two objectives are combined with a weight, and a sensitivity analysis shows the impact of the weight on both objectives to provide managerial guidance. The resulting raise amounts satisfy both internal alignment and external competitiveness conditions and represent employee performance and potential for promotion. The proposed mixed integer programming problem can be solved with commercial solvers quickly, even for rather large instances. The short computational time directly addresses the challenge raised by the current trend that more enterprises hire a large number of exempt employees. Additionally, two cases are presented with detailed data collection to illustrate the applications and limitations of the proposed model.